Manganese modulates hepatocellular carcinoma cytotoxicity and doxorubicin sensitivity in a dose dependent manner - Wang, Hao-lun; Fan, Qian-qing; Tang, Ting; He, Zi-yun; Xie, Yu-an; Liu, Zhi-hui (Frontiers in Oncology, 2026)
IntroductionHepatocellular carcinoma (HCC) is a leading cause of cancer-related mortality globally, characterized by decreased manganese (Mn) levels in tumor tissues compared to noncancerous liver tissues. Although manganese’s role in enhancing immune responses and inhibiting tumor growth has been noted, its specific contribution to HCC development and its influence on drug sensitivity are not well defined.MethodsWe assessed the viability of HCC cells treated with various concentrations of MnCl2 using assays such as CCK-8, EdU staining, and flow cytometry. These assays revealed that MnCl2 at different concentrations could reduce doxorubicin sensitivity or induce cytotoxicity. Subsequently, transcriptome sequencing was employed to identify differentially expressed genes and those playing critical roles. The potential molecular mechanisms were investigated through functional enrichment analysis, and key genes were validated using Western blot (WB) analysis.ResultsOur study found that low MnCl2 concentrations increased AKT pathway phosphorylation, enhancing doxorubicin resistance, while high MnCl2 concentrations activated the P53 pathway and immune response, downregulating mitosis and the MYC pathway.DiscussionThis research elucidates the impact of Mn²+ concentration on HCC cell behavior, offering a theoretical basis for Mn²+’s potential use in HCC treatment. The findings contribute to a deeper understanding of Mn²+’s role in HCC and may inform future therapeutic strategies.